Vaccination against HBV and HAV as Mode of Hepatitis Prevention among People Living with HIV-Data from ECEE Network Group - Aimla, Kerstin; Kowalska, Justyna Dominika; Matulionyte, Raimonda; Mulabdic, Velida; Vassilenko, Anna; Bolokadze, Natalie; Jilich, David; Antoniak, Sergii; Oprea, Cristiana; Balayan, Tatevik; Harxhi, Arjan; Papadopoulos, Antonios; et al. (Vaccines, 2023)
(1) Background: Viral hepatitis C (HCV) and viral hepatitis B (HBV) are common co-infections in people living with HIV (PLWH). All PLWH should be vaccinated against HBV and hepatitis A (HAV) and treated for HBV and HCV. We aimed to compare testing, prophylaxis and treatment of viral hepatitis in PLWH in Central and Eastern Europe (CEE) in 2019 and 2022. (2) Methods: Data was collected through two on-line surveys conducted in 2019 and 2022 among 18 countries of the Euroguidelines in CEE (ECEE) Network Group. (3) Results: In all 18 countries the standard of care was to screen all PLWH for HBV and HCV both years; screening of HAV was routine in 2019 in 54.5% and in 2022 47.4% of clinics. Vaccination of PLWH against HAV was available in 2019 in 16.7%, in 2022 in 22.2% countries. Vaccination against HBV was available routinely and free of charge in 50% of clinics both in 2019 and 2022. In HIV/HBV co-infected the choice of NRTI was tenofovir-based in 94.4% of countries in both years. All clinics that responded had access to direct-acting antivirals (DAAs) but 50% still had limitations for treatment. (4) Conclusions: Although testing for HBV and HCV was good, testing for HAV is insufficient. Vaccination against HBV and especially against HAV has room for improvement; furthermore, HCV treatment access needs to overcome restrictions.